Radial extracorporeal shock wave therapy alters plantar pressure distribution in chronic plantar fasciitis: a biomechanical analysis - Shang, He; Ma, Tao; Wei, Yuan; Yang, Tianxiang; Liang, Jinpeng; Liu, Xueqi; Li, Jun; Wang, Yi; Chen, Desheng (Frontiers in Rehabilitation Sciences, 2026)
ObjectiveThis study aimed to investigate the impact of radial extracorporeal shockwave therapy (rESWT) on plantar pressure distribution in patients with chronic plantar fasciitis (PF). While prior research has established rESWT's clinical efficacy in pain relief, its specific biomechanical effects on plantar loading patterns remain less quantified. This study addresses that gap by providing objective pedobarographic evidence of rESWT-induced pressure redistribution.MethodsA cohort of 42 patients with unilateral chronic PF was enrolled. Plantar pressure parameters—including total foot pressure, forefoot pressure, rearfoot pressure, peak pressure point, mean pressure, and contact area—were assessed using a plantar pressure measurement system before and after a standardized rESWT protocol. Evaluations compared the affected limb with the contralateral unaffected limb.ResultsFollowing rESWT, significant changes were observed: on the affected side, forefoot pressure increased (p = 0.001) and rearfoot pressure decreased (p = 0.001); on the unaffected side, forefoot pressure also increased (p = 0.002) and rearfoot pressure decreased (p = 0.003). Total foot pressure decreased on the affected side (p = 0.032) but increased on the unaffected side (p = 0.032). Contact area increased significantly only on the unaffected side (p < 0.001). No significant alterations were found in peak pressure point location or mean pressure (p > 0.05). Effect size analysis (Cohen's d > 0.5) confirmed clinically meaningful improvements in forefoot and rearfoot pressure shifts.ConclusionrESWT effectively ameliorates abnormal plantar pressure distribution in PF patients, promoting a forward shift in the pressure center and improving gait symmetry. These findings provide a biomechanical rationale for its clinical use. Future studies should incorporate patient-reported outcomes and longer follow-up to link these biomechanical changes to functional improvement.